2010
DOI: 10.1515/jpm.2010.040
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ureaplasmas by the polymerase chain reaction in the amniotic fluid of patients with cervical insufficiency

Abstract: Aims The purpose of this study was to determine the clinical significance of detecting microbial footprints of ureaplasmas in amniotic fluid (AF) using specific primers for the polymerase chain reaction (PCR) in patients presenting with cervical insufficiency. Methods Amniocentesis was performed in 58 patients with acute cervical insufficiency (cervical dilatation, ≥1.5 cm) and intact membranes, and without regular contractions (gestational age, 16–29 weeks). AF was cultured for aerobic and anaerobic bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 50 publications
4
107
1
2
Order By: Relevance
“…However, recent publications have demonstrated that bacterial culture had a lower rate of detection (27.1%) compared to PCR (up to 72.9%) [35,40]. The use of amniotic fluid culture alone could miss up to 91% of genital mycoplasma [41]. PCR methodology offers a number of advantages over bacterial culture techniques: species-and serovar-specific identification even in the absence of viable organisms (positivity even after antibiotic treatment), higher sensitivity and quicker results (within 24 h).…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent publications have demonstrated that bacterial culture had a lower rate of detection (27.1%) compared to PCR (up to 72.9%) [35,40]. The use of amniotic fluid culture alone could miss up to 91% of genital mycoplasma [41]. PCR methodology offers a number of advantages over bacterial culture techniques: species-and serovar-specific identification even in the absence of viable organisms (positivity even after antibiotic treatment), higher sensitivity and quicker results (within 24 h).…”
Section: Inflammationmentioning
confidence: 99%
“…After the occurrence of the PPROM in the second trimester, bacteria rapidly colonize the surfaces of amniotic membrane, chorion, decidua, fetal skin and mucosa, as well as the umbilical cord (Figure 3). The PCRbased assays for bacterial presence in the amniotic fluid have a superior sensitivity compared to standard culture methods and the positive predictive value for predicting the incidence of neonatal complications of 60% vs. 35% for the standard test [41,84,85]. Walker et al [86] found that only 33% of infants remained undelivered after one week following a PPROM history.…”
Section: Maternal and Neonatal Outcomesmentioning
confidence: 99%
“…However, the risk of adverse pregnancy outcome after emergency cerclage seems to be increased also among those with no detectable amniotic fluid infection but with a latent intra-amniotic inflammatory process. Several markers of intra-amniotic inflammation have been shown to predict early cerclage failure and impending delivery including IL-6, metalloproteinase-8, glucose concentration, CRP, white blood cell, LDH and neutrophil counts [4,5,8,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…The patient agreed to undergo a preliminary amniocentesis in order to exclude an actual amniotic infection and to proceed with the emergency cerclage only if negative results were obtained. Then, we retrieved 10 ml of clear amniotic fluid and obtained the following results within 12 h: normal glucose level (19 mg/dl), interleukin-6 (IL-6; 8.68 ng/ml), CRP (<0.03 mg/dl; normal values <0.6 mg/dl [8]; the CRP level was measured with a latex-enhanced turbidimetric immunoassay). A sample was additionally sent for culture (bacteria and Mycoplasma ) to the Microbiology Department.…”
Section: Case Reportmentioning
confidence: 99%
“…Various findings suggest that in some pregnancies, the infective organism may be present in placental tissues from mid-gestation. In fact, it has been suggested that intrauterine infections may originate pre-conceptually, possibly arising from organisms residing in the endometrium prior to implantation which subsequently activate the maternal innate immune system as a result of a change in growth or immune surveillance (Oh et al, 2010). It is possible that an altered cytokine expression can cause per se preterm labor, namely an overproduction of cytokines can be harmful to the fetus because of the activation of the cytokine flow (Vrachnis et al, 2010).…”
Section: Interactions With Environmental Factorsmentioning
confidence: 99%